2008
DOI: 10.1080/00048400701846608
|View full text |Cite
|
Sign up to set email alerts
|

Humean dispositionalism

Abstract: Humean metaphysics is characterised by a rejection of necessary connections between distinct existences. Dispositionalists claim that there are basic causal powers. The existence of such properties is widely held to be incompatible with the Humean rejection of necessary connections. In this paper I present a novel theory of causal powers that vindicates the dispositionalist claim that causal powers are basic, without embracing brute necessary connections. The key assumptions of the theory are that there are na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…12 These activities might turn out to be nothing more than acquisitions of further powers by the objects involved (so claims the pandispositionalist), but Lowe rejects this possibility arguing that some of the activities must be 'pure' in the sense that they do not consist merely in the acquisition of further powers (2010: 10). 13 For instance, Ellis (2001) and Handfield (2008) treat manifestations as processes, McKitrick (2010) as effects. Molnar (2003) and Mumford (2009) offer non-event type views.…”
Section: Overstretching Single-track Powersmentioning
confidence: 98%
“…12 These activities might turn out to be nothing more than acquisitions of further powers by the objects involved (so claims the pandispositionalist), but Lowe rejects this possibility arguing that some of the activities must be 'pure' in the sense that they do not consist merely in the acquisition of further powers (2010: 10). 13 For instance, Ellis (2001) and Handfield (2008) treat manifestations as processes, McKitrick (2010) as effects. Molnar (2003) and Mumford (2009) offer non-event type views.…”
Section: Overstretching Single-track Powersmentioning
confidence: 98%
“…Causal relations are not a simple pattern of regular contiguous co-instantiations of properties of the same types, but one property token literally produces or brings about other property tokens and thus is the ground of the existence of those other property tokens. However, in recent literature, doubts are expressed as to whether in case one conceives the fundamental properties as dispositions and thus in a causal manner, one inevitably is committed to recognizing necessary connections in the world, thereby contradicting Humean metaphysics (Handfield 2008, Anjum & Mumford 2009.…”
Section: Causal Propertiesmentioning
confidence: 99%
“…I take this structural property proposal to be more promising than the conjunctive property proposal, and interestingly Handfield (2008) has suggested that appealing to the notion of a structural property may help Humean metaphysicians make sense of dispositional properties. Perhaps, then, trope theorists or Aristotelians could carry this kind of insight over to the dispositionalist view.…”
Section: Manifestations As Structural Constituents: the Diachronic Prmentioning
confidence: 99%